The importance of women's status for child nutrition in developing countries - Smith, Lisa C.; Ramakrishnan, Usha; Ndiaye, Aida; Haddad, Lawrence J.; Martorell, Reynaldo (International Food Policy Research Institute, 2003)
One in every three preschool-aged children living in developing countries is malnourished. This disturbing yet preventable state of affairs causes untold suffering and, given its wide scale, is a major obstacle to the development process itself. Volumes have been written about the causes of child malnutrition and the actions that can be taken to reduce it— ranging from community-based feeding programs to accelerated economic growth (Smith and Haddad 2000). Until recently, too little attention has been paid to an obviously relevant yet little noticed issue: the role that the capabilities and well-being of children’s caretakers, usually their mothers, play in children’s nutritional well-being. This issue is the subject of this study.